2021
DOI: 10.1124/jpet.120.000166
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Glucose-6-Phosphate Dehydrogenase Activity Attenuates Right Ventricle Pressure and Hypertrophy Elicited by VEGFR Inhibitor + Hypoxia

Abstract: Pulmonary hypertension (PH) is a disease of hyperplasia of pulmonary vascular cells. The pentose phosphate pathway (PPP)a fundamental glucose metabolism pathwayis vital for cell growth. Because treatment for PH is inadequate, our goal was to determine whether inhibition of glucose-6-phosphate dehydrogenase (G6PD), the rate-limiting enzyme of the PPP, prevents maladaptive gene expression that promotes smooth muscle cell (SMC) growth, reduces pulmonary artery remodeling, and normalizes hemodynamics in experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…The interventions of specific enzymes to restore the abnormal metabolism open a new avenue for the treatment of PH. For example, inhibitor of glucose-6-phosphate dehydrogenase, a rate-limiting enzyme in pentose phosphate pathway, was reported to modulate DNA methylation and alleviate pulmonary artery remodeling (Kitagawa et al, 2021). Sphingosine kinases 1 (SphK1) is determinant for the synthesis of sphingosine-1-phosphate, an critical mediator for cell proliferation, migration and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The interventions of specific enzymes to restore the abnormal metabolism open a new avenue for the treatment of PH. For example, inhibitor of glucose-6-phosphate dehydrogenase, a rate-limiting enzyme in pentose phosphate pathway, was reported to modulate DNA methylation and alleviate pulmonary artery remodeling (Kitagawa et al, 2021). Sphingosine kinases 1 (SphK1) is determinant for the synthesis of sphingosine-1-phosphate, an critical mediator for cell proliferation, migration and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a separated group, mice received daily subcutaneous injections of a novel G6PD inhibitor, N-[(3β,5α)-17-oxoandrostan-3-yl]sulfamide (4091; 1.5 mg kg −1 day −1 ) ( 32 ), for last 3 weeks of hypoxia. We have recently found that 4091 treatment inhibits G6PD activity in lungs of mice exposed to hypoxia ( 33 ). Mice were also intratracheally administered aerosolized AdGFP-G6PD-shRNA (IT-shG6PD), which reduces expression of G6PD, or AdGFP-scrambled-shRNA (given once a week) during weeks 3 and 4 ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that G6PD deficiency may protect against the development of PAH. Indeed, inhibition and knockdown of G6PD in chronic hypoxia-induced PAH and SuHx-PH rat models reverses the metabolic changes, epigenetic modification (DNA methylation), maladaptive expression of genes that contribute to PA remodeling, the formation of occlusive lesions, and RV pressure overload [ 70 , 71 , 72 , 73 ]. Protein kinase G1 (PKG1) signaling has a vital role in this process, as G6PD inhibition evokes PKG1α-dependent signaling, thereby mediating expression of contractile proteins, reducing Ang II-induced contraction and proinflammatory factor in PA response to hypoxia [ 66 , 74 , 75 ].…”
Section: Mitochondrial Metabolic Pathways In Pulmonary Hypertensionmentioning
confidence: 99%